Low-Code Platform for Health Protocols Implementation in Sabilussalam Mosque During The COVID-19 Pandemic - Sofia Umaroh; Kurnia Ramadhan Putra; nur Fitrianti; Mira Musrini Barmawi (Institut Teknologi Nasional, Bandung, 2022)
The COVID-19 pandemic condition has changed various aspects of life, especially Muslims’ prayer activities. COVID-19 pandemic has especially affected mosques as a place for Muslims to pray five times a day and to have Friday prayer congregation. To prevent the spread of COVID-19, the Sabilussalam Mosque located at Jl. Dr. Hatta Bandung has restricted its capacity and ensured visitors’ body temperature below 37,4 C manually. However, physical contact still occured, and its capacity still exceeded 50%. Therefore, the adoption of self-check temperature and automatic capacity counter as a method of mitigating the COVID-19 pandemic in mosques was needed. This community service aims at implementing a system for controlling mosque capacity and for avoiding physical contact during praying. The Low Code-based app counts temperature data broadcasted by K3 Pro and stored in NowDB cloud-service. As a result, the system manages to control the mosque's capacity to a maximum of 50% without any physical contact because it relies on internet connection.